Functional abnormalities of the right posterior insula are related to the altered self-experience in schizophrenia. (30th October 2016) - Chen, Xi; Duan, Mingjun; He, Hui; Yang, Mi; Klugah–Brown, Benjamin; Xu, Hao; Lai, Yongxiu; Luo, Cheng; Yao, Dezhong
Abstract: The insula is involved in detecting the salience of internal and external stimuli, and it plays a critical role in psychosis. Previous studies have demonstrated the structural and functional alterations of the insula in schizophrenia. To acquire a full picture of the functional alterations of the insula in schizophrenia, the resting-state fMRI data of 46 patients with schizophrenia and 46 healthy control subjects were collected. We used clustering analysis to divide the insula into three subregions: the dorsal anterior insula (dAI), ventral anterior insula (vAI) and posterior insula (PI). Then, whole-brain functional connectivity analysis was conducted based on these subregions. The results showed that the right dAI and PI in patients exhibited altered functional connections with the primary sensorimotor area. In addition, the right PI of the patients exhibited increased functional correlations with the thalamus. More importantly, the altered functional properties of the right PI were significantly correlated with the severity of the delusion and poor insight in schizophrenia. The results suggested that the right PI might play an important role in self-experience processing in schizophrenia. Accordingly, the right PI should be considered very important in the pathological mechanism of schizophrenia. Highlights: DAI and PI in patients exhibited altered functional connection with sensorimotor area. The right PI of patients showed increased functional correlation with the thalamus. These altered functional properties related to the altered self-experience in patients.